Analysis of Error in Solving Story Problems on Mixed Counting Operations for Class Iv Elementary School - Khotimah, Wonadesma Dwi; Sary, Ryky Mandar; Herman, Tatang; Prabawanto, Sufyani (IndoMath: Indonesia Mathematics Education, 2023)
This research focus is on the ability to solve word problems on mixed arithmetic operations. The research objective is to analyze errors in solving word problems in mixed arithmetic operations material. Furthermore, this research approach was qualitative research. The data sources were 10 fourth-grade students and a fourth-grade teacher at State Elementary School 1 Sulursari; teachers were chosen because of their role in learning. Data collection procedures consisted of tests and interviews. The research showed that fourth-grade students experienced errors in solving word problems on mixed arithmetic operations, including reading, transformation, process skills, and final answer writing errors. The suggestions conveyed to students when learning should pay attention to the teacher when explaining the material well so that they can ask the teacher when they don't understand the material. Multiply practice questions so that you know better when working on questions; you should carefully not need to rush.